Projetos diversos - JUNQUEIRA, Thiago Felipe; CUNHA JÚNIOR, Marco Antonio Aves da; GRACIANO, Lucas José Landim Saturno; SILVA, João Felipe dos Santos; GONÇALVES, Otávio Augusto (077, 2024)
Inovação e normas corrigem deficiências e implementammelhoriasemprojetos já existentes em um método denominado kaizen. A análise dosprojetosexistentes, somado com um bom planejamento e programação dita aeficáciadasmelhorias aplicadas. O kaizen ferramenta de melhoria continua nos induzanovospensamentos em um princípio de inovação, tecnologia, agilidade, produtividadeesegurança.

These innovations and standards correct deficiencies andimplementimprovements in existing projects, in a method called kaizen. The analysis of existingprojects, combined with good planning and programming dictates the effectivenessofthe improvements applied. The kaizen continuous improvement tool inducesustonew thoughts based on the principle of innovation, technology, agility, productivityand safety
Miscellaneous projects
Keywords: Inovação; Projetos; Controle e Processos Industriais